2021
DOI: 10.1039/d1na00238d
|View full text |Cite
|
Sign up to set email alerts
|

Photophysical properties and fluorescence lifetime imaging of exfoliated near-infrared fluorescent silicate nanosheets

Abstract: The layered silicates Egyptian Blue (CaCuSi4O10, EB), Han Blue (BaCuSi4O10, HB) and Han Purple (BaCuSi2O6, HP) emit as bulk material bright and stable fluorescence in the near-infrared (NIR), which is...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(47 citation statements)
references
References 60 publications
0
47
0
Order By: Relevance
“…An example for remote imaging are NIR fluorescent nanosheets, which were remotely detected in a customized portable setup [171, 188] . Due to the high brightness and emission closer to the visible range (910 nm), a low‐cost CMOS camera (Complementary Metal Oxide Semiconductor, Si based), which typically has a low quantum efficiency of around 5 % in the NIR region, could be used here.…”
Section: Swcnt‐based Sensorsmentioning
confidence: 99%
“…An example for remote imaging are NIR fluorescent nanosheets, which were remotely detected in a customized portable setup [171, 188] . Due to the high brightness and emission closer to the visible range (910 nm), a low‐cost CMOS camera (Complementary Metal Oxide Semiconductor, Si based), which typically has a low quantum efficiency of around 5 % in the NIR region, could be used here.…”
Section: Swcnt‐based Sensorsmentioning
confidence: 99%
“…neurotransmitters 15,16 ), their established separation 10,17 and functionalization routes 8,18 , as well as the possibility to perform defect chemistry [19][20][21] . 2D materials such as exfoliated silicate nanosheets (NS), on the other side, stand out for their high fluorescence brightness and remarkable photostability, which make them very promising labelling agents for multiple bioimaging scenarios 22,23 . Organic fluorophores tend to have shorter emission wavelengths and limited solubility in water but they also display faster excretion kinetics and can be chemically tailored, which makes them versatile materials for bioimaging 6 .…”
Section: Introductionmentioning
confidence: 99%
“…This calcium copper tetrasilicate displays a layered crystal structure which allows to prepare nanosheets (NS) via simple stirring in hot water [22][23][24][25][26][27] . Most interestingly, it has been shown that the bright, stable and long-lived nearinfrared (NIR) fluorescence of the bulk material (λem ≈ 910-930 nm) [25][26][27][28][29][30] is preserved in exfoliated NS down to just few tenths of nm in size 31,32 . The biocompatible nature of this class of layered silicates has been demonstrated by cell viability assays and in vivo studies 31 .…”
Section: Introductionmentioning
confidence: 99%
“…The biocompatible nature of this class of layered silicates has been demonstrated by cell viability assays and in vivo studies 31 . Among them, an increasing number of publications has proven the high potential of EB-NS in the biomedical field as multi-functional platform for bioimaging 31,32 , sensing 33 , photothermal therapy (PTT) 34,35 , tissue engineering 36,37 and more. Especially as novel NIR fluorophore, EB-NS appears of extreme interest.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation